Late Ottoman period preventive health institutions in Istanbul: an architectural approach - Gider, Sumeyye; Unal, Zeynep Gul (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The preventive health institutions were founded in Istanbul as a result of the Ottoman Empire's policy to fight epidemic diseases that affected all parts of the world in the nineteenth century. The purpose of this paper is to examine the historical and current state of these heritage buildings. Design/methodology/approach Through the original documents, photographs and floor plans dating nineteenth and early twentieth century obtained from the Ottoman State Archives, historical development and architectural features of the buildings have been identified. And the original geographical locations of the buildings, especially the destroyed ones, are investigated by the historic maps. Plan and facade features, construction techniques are examined according to the information gained from the newspapers, journals and health annuals of the period. Findings This paper presents the findings of an MSc thesis conducted on the historical approach of preventive health institutions and preservation problems of the Pendik Institute of Veterinary Bacteriology. In the study, it has been examined that institutes in five different functions which were established after the foundation of the Quarantine Council in 1838 with parallel to the course of epidemics and scientific development in the West. In Istanbul, eight quarantine stations, three disinfection stations, one rabies laboratory, one vaccination institute and five bacteriology institutes have been documented. Some of these institutions fell out of use due to the loss of their original function and have been abandoned and demolished, some of them have survived with functional changes. The extant samples of these preventive health institutions are studied on the purpose of investigating their conditions of preservation. Originality/value Late Ottoman period preventive health institutions in Istanbul have been the subject of the researches within the field of medicine and science history to date. There is no study in Turkish and International literature discussing these institutions in terms of architecture. In the study these buildings have been thoroughly examined based on their architectural features and heritage values. The glass plate photographs of the Pendik Institute of Veterinary Bacteriology, floor plans and some photographs of the other institutions which are obtained from Ottoman State Archives and newspapers of the period have been published for the first time in this paper.
Keywords: Preventive health institutions; Pandemic; Late ottoman period; Cultural heritage; Istanbul; Healthcare architecture; Science & Technology - Other Topics